Efficiency Measurement and Modeling of a High‐Performance Mg2(Si, Sn)‐Based Thermoelectric Generator. Issue 1 (17th July 2022) - Camut, Julia; Ziolkowski, Pawel; Ponnusamy, Prasanna; Stiewe, Christian; Mueller, Eckhard; de Boor, Johannes
Abstract : Mg2 (Si, Sn) is an attractive material class due to its excellent thermoelectric (TE) properties, its eco‐friendly constituents, its low mass density, and its low price. A lot of research has been done on optimizing its TE properties; however, works on its use in thermoelectric generators (TEG) are scarce. Herein, the first conversion efficiency measurement of a functional, fully Mg2 (Si, Sn)‐based TEG, approaching a maximum value of 4% for an applied Δ T = 375 °C, is shown. A maximum power density of 0.9 W cm − 2 (related to the cross‐sectional area of the TE legs) at Δ T =375 °C is also reported, which is among the highest performance of silicide‐based modules reported in literature. Efficiency measurements can be tricky due to the uncertainty of heat flow measurement and parasitic heat losses; therefore, assessing the measurement reliability by confronting it to theoretical calculations is necessary. TEG device simulation in a constant property model is used to compare measured data to expected values and a good match is found (<1% deviation for current at maximum power, <4% difference for maximum power output, deviation within measurement uncertainty range for heat flows and efficiency). The significant discrepancy between measurement and calculations of the inner electrical resistance reveals room for improvement. Cracks form due to thermally induced mechanical stress, which dramatically increase the inner electrical resistance. It is shown that by avoiding those cracks, the maximum power output and conversion efficiency of the TEG could be improved by 30%. Abstract : Herein, the fabrication of an ecofriendly, cheap, and lightweight thermoelectric generator (TEG), made n‐ and p‐type Mg2 (Si, Sn), is given. The first efficiency measurement of such a device is shown and a high‐performance power density among silicide‐based TEGs reported in literature is reported. Finally, measurement by comparing data to theoretical predictions and identifying room for future improvement are verified.